2010
DOI: 10.1111/j.1420-9101.2010.01982.x
|View full text |Cite
|
Sign up to set email alerts
|

Egg phenotype differentiation in sympatric cuckooCuculus canorusgentes

Abstract: The brood parasitic common cuckoo Cuculus canorus consists of gentes, which typically parasitize only a single host species whose eggs they often mimic. Where multiple cuckoo gentes co-exist in sympatry, we may expect variable but generally poorer mimicry because of host switches or inter-gens gene flow via males if these also contribute to egg phenotypes. Here, we investigated egg trait differentiation and mimicry in three cuckoo gentes parasitizing great reed warblers Acrocephalus arundinaceus, marsh warbler… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
64
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(65 citation statements)
references
References 64 publications
1
64
0
Order By: Relevance
“…the host-specific mimicry [5]. In a recent study, we found that several aspects of the egg phenotype, including both colour and size differ significantly among our three host races [43]. However, this phenotypic variation does not generate three distinctly different morphs, because the three host races overlap in colour space.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…the host-specific mimicry [5]. In a recent study, we found that several aspects of the egg phenotype, including both colour and size differ significantly among our three host races [43]. However, this phenotypic variation does not generate three distinctly different morphs, because the three host races overlap in colour space.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, we have no information regarding size differentiation between the corresponding cuckoo host races. However, their eggs vary in size, demonstrating size mimicry with their specific host species [43]. Since larger birds generally lay larger eggs [47], it is reasonable to suppose that cuckoos parasitizing the small marsh warbler are smaller than those parasitizing the much larger great read warbler and corn bunting.…”
Section: Discussionmentioning
confidence: 99%
“…For example, brood parasitic Vidua finches, Vidua spp., underwent sympatric speciation as they annexed novel host species [15]. Moreover, specialization on particular host species has led to genetic divergence within some cuckoo and honeyguide species into distinct host-specific races [16][17][18], and Krü ger et al [19] demonstrated that species of parasitic cuckoos had more subspecies than species of non-parasitic cuckoos. Since the appearance of these studies, novel phylogenies [20] and phylogenetic methods [3,21] have been developed.…”
Section: Introductionmentioning
confidence: 99%
“…The common cuckoo is characterized by a large number of host races that each specializes on a particular host species to which its eggs are adapted in terms of coloration, spottiness (e.g. [8,9]) and egg size [9 -11]. The timing of breeding may vary among host races simply because different host species reproduce at different times [2,12].…”
Section: Introductionmentioning
confidence: 99%